(untitled) (Physical Culture and Sport: Scientific Perspective, 2026)
Education is regarded as a fundamental tool for preventing anti-doping rule violations and as a strategic direction in developing a culture of integrity in sport. Considering the updated requirements of the World Anti-Doping Code and the provisions of the International Standard for Education (ISE), the study of the state, trends, and challenges of anti-doping education in Ukraine is of particular relevance. Coaches occupy a central position within the sports community, performing not only organizational and methodological but also educational and moral functions. They create the athlete’s immediate learning environment, influence value formation, motivation for training, and adherence to fair play principles. Therefore, exploring the level of coaches’ anti-doping awareness and their readiness to integrate anti-doping components into training systems is a prerequisite for building an effective national framework of anti-doping education. Purpose. To determine the current state of anti-doping education, analyze coaches’ attitudes toward its content and effectiveness, and outline directions for its improvement in Ukraine. Methods. A survey of 131 coaches representing 46 sports was conducted online (via Google Forms). Methods included questionnaires, analysis of scientific and methodological literature, and statistical data generalization. Results. Coaches acknowledge their key role in shaping athletes’ anti-doping culture and support the integration of relevant educational components into training programs, primarily through the activities of sports federations, clubs, and educational institutions. Participation in educational programs is perceived as an integral part of professional activity that requires continuous professional development. While coaches positively assess digital learning tools, they prefer interactive and practice-oriented forms of education that ensure deeper knowledge acquisition and the development of applied skills. However, uneven participation in educational activities, insufficient institutional coordination, and limited coverage of technical and legal aspects of anti-doping activities were identified. Conclusions. Coaches demonstrate a strong sense of responsibility in fostering a culture of “clean sport” and show readiness to engage in educational initiatives. The development of anti-doping education requires a transition from isolated activities to a comprehensive system combining digital resources with interactive learning methods, ensuring consistent collaboration among the National Anti-Doping Center (NADC), sports federations, and educational institutions within a unified educational framework.